2013
DOI: 10.1039/c3cp52958d
|View full text |Cite
|
Sign up to set email alerts
|

A coarse-grained model for polyethylene glycol in bulk water and at a water/air interface

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 67 publications
6
40
0
Order By: Relevance
“…A set of CG potentials was derived by successively adjusting the different potential contributions in the order of their relative strengths, which are U stretch , U bend , U nonbonded , and U dihedral . Choosing this order is the most efficient way for obtaining CG potentials with the IBI technique since it has been shown from the previous works that the intramolecular degree of freedoms can be treated almost independently from intermolecular ones [22,36,37]. Figure 2 shows an excellent match of the bond-, angle-and dihedral angle distributions.…”
Section: Resultsmentioning
confidence: 76%
“…A set of CG potentials was derived by successively adjusting the different potential contributions in the order of their relative strengths, which are U stretch , U bend , U nonbonded , and U dihedral . Choosing this order is the most efficient way for obtaining CG potentials with the IBI technique since it has been shown from the previous works that the intramolecular degree of freedoms can be treated almost independently from intermolecular ones [22,36,37]. Figure 2 shows an excellent match of the bond-, angle-and dihedral angle distributions.…”
Section: Resultsmentioning
confidence: 76%
“…Examples include the study of interactions of polymers with single-walled carbon nanotubes [3,4], the prediction of solubility of pharmaceutical compounds in polymeric carriers [5] and the study of structure and mechanics of glassy polymers [6]. Moreover, by exploiting coarse graining potentials, polymer simulation studies have been brought to a mesoscale level [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while previous molecular modeling studies have been reported for polymer hydrogels using all-atom models, [13][14][15][16][17][18] CG models, [19][20][21][22][23]28,31,33,[36][37][38][39][40] and lattice models, [24][25][26][27] each of these individual methods has its own unique limitations. As an approach to overcoming the limitations of each individual method, composite modeling schemes have been devised to bridge models at different levels in order to generate wellrelaxed atomistic models.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical schemes have also been developed specifically for PEG-based systems; examples include studies of the conformation and hydrodynamics of PEG, 28 the interfacial properties of PEG surfactant/water, [30][31][32] PEG-contained proton exchange membranes, 22 PEG-lipid systems, 29 and the development of kinetic models to predict growth, cross-link density profiles, and the level of ligand incorporation for PEG hydrogels. 33 Molecular simulations have also been recently conducted to study the behavior of an individual peptide-polymer a) Electronic mail: latourr@clemson.edu conjugated chain to examine the influence of the polymer backbone on the conformation of a tethered peptide chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation